Model NOAH: Rekonstruksi Kesalehan Kristen dalam Budaya Media Sosial melalui Pembacaan Ulang Narasi Nuh dan Digital Theology - Ronal Riki Lego (Sekolah Tinggi Teologi Bethel Ambon, 2024)
The rapid growth of social media has created a new cultural environment that significantly shapes identity formation, communication patterns, and religious practices in contemporary society. Within this context, Christians face the challenge of maintaining authentic piety amid a digital culture characterized by social validation, identity fragmentation, and algorithmic influence. This study aims to reconstruct Noah’s piety in Genesis 6–9 as a theological paradigm for Christian life in the age of social media through the lens of Heidi A. Campbell’s Digital Theology. Employing a qualitative library research approach, the study integrates biblical textual analysis with contemporary Digital Theology scholarship. The findings reveal that Noah’s piety was rooted in a consistent relationship with God, resulting in integrity, obedience, authentic identity, and transformative witness. The study further demonstrates that Christian piety in the digital age should not be defined primarily by visibility, popularity, or social influence, but by faithfulness to God in all forms of digital engagement. As its primary theoretical contribution, this research proposes the NOAH Model (Networked Integrity, Obedient Presence, Authentic Identity, and Holy Witness) as a paradigm for Christian piety in the digital era. This model integrates biblical theology, Digital Theology, digital ethics, and Christian discipleship into a unified conceptual framework for cultivating an authentic, critical, and transformative digital spirituality.